Customized vacuum assisted closure therapy of wounds as a simple and cost-effective technique of wound closure-a prospective observational study from underdeveloped world - Mir, Mushtaq A.; Wani, Tajdin; Khan, Tahir Saleem; Shah, Syed Mushtaq Ahmad; Kumar, Ravi; Naikoo, Zahoor Ahmed; Bhat, Bashir Ahmed (International Journal of Research in Medical Sciences, 2021)
Background: Aim of the study was to study the efficacy and cost-effectiveness of indigenously designed customized vacuum assisted closure (VAC) of wounds in our patients. The management of difficult to heal wounds has been the main force that led to the development of advanced gadgets for their management. The technique of vacuum assisted closure has revolutionized the management of difficult to heal wounds and delivers better results as compared to conventional technique. Our aim was to assess the efficacy and cost effectiveness of customized VAC therapy. Methods: This prospective study was conducted in the department of surgery and allied specialties, GMC Srinagar, from June 2018 and September 2020. During this period, 80 patients were subjected to VAC therapy and were included in this study. Results: VAC dressing was used in 80 patients. 55 were males and 25 were females. Most of the wounds in our study were located over lower limbs (70%). RTA was the most common mode of injury followed by fall from height. After the VAC therapy, 78.8% patients were managed by STSG, 11.3% by flap cover, 6.3% by secondary suturing and 3.8% healed by secondary intention. Pain was experienced by 30% of the patients, 7.5% had hypoalbuminemia, 3.8% had surrounding skin maceration. The average total cost of the VAC therapy was 863.13 (±399.82) Indian rupees (11.76 USD). The mean duration of hospital stay for our patients was 22 days. Conclusions: Customized VAC Therapy has revolutionary potential in the management of the difficult to treat wounds as far as its safety, speed and cost effectiveness is considered especially in a setup of poor income nations like ours.